PEMBELAJARAN ANSAMBEL TALEMPONG PACIK MENGGUNAKAN MEDIA AUDIO VISUAL DI KELAS X TBSM SMK MUHAMMADIYAH 1 PADANG - Muhamad Aldi Kusuma; Irdhan Epria Darma Putra (Universitas Negeri Padang, 2026)
This study aims to describe the learning process of the Talempong Pacik ensemble using audiovisual media in the X grade of the Motorcycle Business Engineering (TBSM) program at SMK Muhammadiyah 1 Padang. This research uses a qualitative approach with a descriptive method based on educational phenomenology. The research subjects consist of cultural arts teachers and X grade TBSM students, while the research object is focused on the learning process of the Talempong Pacik ensemble. Data collection techniques were carried out through non-participant observation, in-depth interviews, literature studies, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, classification, and drawing conclusions. Research results show that the use of audiovisual media can increase enthusiasm, understanding of Pacik techniques, and rhythm coordination among students in learning the Talempong Pacik ensemble. Audiovisual media play an effective role as a learning model that helps students understand playing techniques independently, especially under conditions of limited time and a limited number of musical instruments. Phenomenologically, students feel comfortable and find it easier to learn because audiovisual media allow for repeated processes of observation, imitation, and internalization of rhythmic patterns. Thus, learning the Talempong Pacik ensemble using audiovisual media can be an effective alternative learning strategy in the context of music education at vocational schools.